Antique Carved Gems: Items for Interaction between Ancient and Modern Art - Micheli, Maria Elisa (Actual Problems of Theory and History of Art, 2017)
Engraved gems are the most remarkable repertoire of iconographic themes from antiquity. Their size allowed them to be carried everywhere in the ancient world and they were available for almost every situation in social life — an extraordinary means of expressing personal beliefs, as well as trends, religious, and political ideologies. The quality of a stone, its cutting-technique, and its subject are versatile performers illustrating the luxurious style of life of ancient societies. Gems have come haphazardly down to our days, sometimes reused into new objects or collected by wealthy amateurs: modern dactyliothecae reproduce the splendor of those in antiquity according the classical sources. Since the Renaissance and occasionally even earlier, in the Middle Ages, gems collecting acts as a metonym for legitimacy and authority. At the same time, gems stimulated philosophical discussions about their magical powers and, on the other hand, they were used by visual artist stimulating inventions for new figurative ideas. If it is difficult to recognize individual patterns deriving from antique carved gems, several prints by Enea Vico and Battista Franco show rich series of intaglios and cameos, creating an impressive ‘visual book’, from which artists could take inspiration. Starting from some subject reproduced by Vico and Franco around the mid-16th century, my paper aims to investigate the appropriation contexts of Dionysiac iconographies turned into convivial processions, triumphs, and allegorical convivial, thus followingthe guide-line provided by Phyllis Pray Bober and John Boardman. While taking into consideration various elements of interest, particular attention has been given to close connections with the concept of ‘firma facilitas’, an ancient-modern system balancing gratia, veritas, and diligentia. This, in turn, supports the arguments in favor of the importance of antique gems in modern visual art and of their artistic recoding.